Refractory Trigeminal Neuralgia: Successful Treatment with LINAC Based Stereotactic Radiosurgery (SRS): First Case in Bangladesh - Yasmin, Taohida; Kumar, Narendra; das, Sandip K; Appasamy, Murugan; Rana, KM Masud; Zafreen, Porama; Kumar, R Arun; Ahsan, Sania (Bangladesh Journal of Neurosurgery, 2020)
Purpose: To present first case of refractory trigeminal Neuralgia treated with SRS in Bangladesh, procedural technique, and outcomes in terms of pain relief. Background: Trigeminal neuralgia (TN), classically known as tic doloureaux is a chronic and recurrent disabling pain syndrome, which described as episodes of lancinating pain over the face along the sensory distribution of trigeminal nerve. First line management of TN is medical with different permutation & combination to control the pain. After the failure of medical management, non-invasive SRS is an established modality to achieve long term pain control. Here, we are reporting a case of TN treated with LINAC based SRS. Case Presentation: A 61 years old, gentleman who developed piercing pain inside his left eye for a duration 1-1.5 sec, precipitated while shaving, brushing teeth in year 2015, occurred 4-5 time a day. He was diagnosed as left TN of V1, started on Carbamazepine, Pregabalin. In 3 years, pain progressed to involve all 3 branches. Even combination Carbamazepine, Gabapentin, Tramadol, Amitriptyline, Clonazepam, & Morphine could not control the pain. Pain was persisting all over the day and he also developed suicidal tendency. Later he has been referred to us for SRS. SRS was done in April-2019, a dose of 90Gy was delivered to the Distal Retrogasserian (RG) also called Marseille point of trigeminal nerve root. Eight months after the SRS patient is almost free of pain without any Medicine. Conclusions: LINAC based SRS is a non-invasive, frameless, and safe procedure with excellent pain control for refractory Trigeminal neuralgia. Bang. J Neurosurgery 2020; 10(1): 123-129